Tinjauan Aspek Keamanan Dan Kerahasiaan Rekam Medis Di Ruang Penyimpanan Rumah Sakit Bhakti Mulia - Annisah Isnaeni; Siswati Siswati (Lembaga Penerbitan Universitas Esa Unggul, 2018)
AbstractSecurity is a method of securing information against access to unauthorized changes. Confidentiality is a limitation of the disclosure of certain personal information. The general objective of this study was to determine the security and confidentiality aspects of medical records in the medical record storage room of Bhakti Mulia Hospital, Jakarta. The specific purpose of this study was to identify the SPO security and confidentiality of medical records in the storage room, identify aspects of security and confidentiality of medical records. The research method used was qualitative with a case study approach to describe how the security aspects and confidentiality of medical records in the storage room of Bhakti Mulia Hospital Jakarta. The technique of collecting data is by observation and interview. The results of the study found, the existence of storage space has not been maintained because of the narrow space, the door is not locked, officers from other parts can enter the storage room. This situation resulted in the medical record being easily lost, the contents of the medical record scattered, and the leakage of the confidentiality of medical records by irresponsible parties. The SPO for security and confidentiality has been established but has not been implemented maximally, which has caused the security and confidentiality aspects of the medical record to not be properly maintained. It is recommended that the SPO be reaffirmed in accordance with government regulations.Keywords: Security and confidentiality, medical records, hospital storage roomsAbstrakKeamanan adalah metode pengamanan informasi terhadap akses perubahan yang tidak sah. Kerahasiaan merupakan pembatasan pengungkapan informasi pribadi tertentu. Tujuan umum penelitian ini untuk mengetahui aspek keamanan dan kerahasiaan rekam medis di ruang penyimpanan rekam medis RS Bhakti Mulia Jakarta. Tujuan khusus penelitian ini adalah mengidentifikasi SPO keamanan dan kerahasiaan rekam medis di ruang penyimpanan, mengidentifikasi aspek keamanan dan kerahasiaan rekam medis. Metode penelitian yang digunakan adalah kualitatif dengan pendekatan studi kasus untuk menggambarkan bagaimana aspek keamanan dan kerahasian rekam medis di ruang penyimpanan Rumah Sakit Bhakti Mulia Jakarta. Teknik pengumpulan data dengan cara observasi dan wawancara. Hasil penelitian yang ditemukan, adanya ruang penyimpanan belum terjaga keamananya karena ruang sempit, pintu tidak terkunci, petugas dari bagian lain dapat masuk ke ruang penyimpanan. Keadaan ini mengakibatkan rekam medis mudah hilang, isi rekam medis tercecer, dan bocornya kerahasiaan rekam medis oleh pihak yang tidak bertanggung jawab. SPO keamanan dan kerahasiaan sudah ada dibuat tetapi belum dilaksanakan dengan maksimal, yang mengabkibatkan aspek keamanan dan kerahasiaan rekam medis belum terjaga dengan baik. Disarankan perlu menegaskan kembali SPO yang telah ditetapkan sesuai peraturan perundangan pemerintah.Kata Kunci: Keamanan dan kerahasiaan, rekam medis, ruang penyimpanan RS